From editorial obligation to procedural accountability: policy approaches to online content in the era of information intermediaries. Issue 2 (4th May 2018) - Bunting, Mark
ABSTRACT: Like all markets, online platforms need rules. Their rules are both explicit, in the form of community standards, moderator guidelines, terms of use, commercial contracts and policies, and implicit, in the code that shapes their interfaces and the algorithms that bring market participants together (Bunting 2018. "'Keeping Consumers Safe Online': Legislating for Platform Accountability for Online Content." Communications Chambers .http://www.commcham.com/keeping-consumers-safe/ ). When platforms – or 'online information intermediaries' – govern the exchange of news, content and speech, their rules raise profound issues of human rights and public welfare. Information intermediaries are not publishers, but neither are they neutral conduits; their role in governing online content markets has inevitable ethical connotations. There has been heated debate about intermediaries' responsibilities with respect to online content. Commentators have alleged that in a wide range of areas, intermediaries' commercial incentives are insufficient to address harmful or illegal content while protecting fundamental rights, and that regulation is required. This paper argues that making intermediaries strictly liable for content they host is not an appropriate solution. Instead policymakers must use new techniques to evaluate and engage with intermediaries' rule-making activities. Where the nature and effects of intermediaries' rules are hard to assess, policymakers may seek their 'procedural accountability'.